Cross Protectivity Analysis of 49.8 kDa Pili Subunits of S. flexneri against Vibrio cholerae Infection - Yuni Nur Hidayati, Dwi; Rully, Septha; Amalia, Aisyah; Larissa Widyani, Elsa; Indraswari, Genitri; Prasetya, Adrian; Soraya, Merika; Winarsih, Sri; Reto Prawiro, Sumarno (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Although the AMV and AMS vaccine candidates have similar characteristics as hemagglutinin and adhesive molecules, there are differences in molecular weight. Objective. The research aims to determine the immunological cross-reaction between AMS and AMV. Method. Antihemagglutination test used the anti-adhesion molecular antibody AMS. Next, we examined the immune response that has to be linked with protectivity. The model of the research uses MLIL. The sample separated the mice into four groups, and each group had five mice. The first group was the negative control group. The second group was given AMV and infected with Shigella flexneri. The third group was immunized with AMV before being exposed to Shigella flexneri. The last group was infected with Vibrio cholerae. The immune response results were evaluated by calculating the weight of MLIL and counting the colony of bacteria. We also examined other AMS immune responses, namely, β-defensin and s-IgA levels. To get the data, we measured the number of Th17 immune effector cells, T-reg, and proinflammatory cytokine IL-17A. Data analysis was performed using ANOVA, independent t-test, Kruskal–Wallis, and Mann–Whitney tests. Results. An antihemagglutination cross immune response, intestinal weight, the number of bacterial colonies, and other findings were found to be significant (p<0.05) for the levels of β-defensin, s-IgA, Th17, T-reg, and IL-17A. Conclusion. The 49.8 kDa·MW protein subunit of the Shigella flexneri adhesion molecule could act as a candidate vaccine homologous for shigellosis and cholera in the future.